(untitled) (African Multidisciplinary Journal of Research, 2022)
Economists, policy makers and business experts agree that the role of SMEs in the economy cannot be underestimated. However, SMEs face various challenges and constraints that inhibit or constraint their sustainability. Researchers have identified conceptual skills among the missing link to successful entrepreneurship. This study sought to establish the effect of conceptual skills on sustainable competitive advantage of food manufacturing SMEs in Kenya. The study used descriptive design that applied systematic and controlled collection of cross sectional data. Quantitative primary data was collected from 106 owners of 123 SMEs firms registered by the Kenya Association of Manufacturers in the food and beverage sub-sector giving a response rate of 86%. The findings showed 5.4% of Sustainable Competitive Advantage of SMEs in food manufacturing in Kenya is attributed to Conceptual Skills with a unit increase in Conceptual Skills increasing Sustainable Competitive Advantage of SMEs in food manufacturing in Kenya by 0. 283. This study established conceptual skills as a contributor to sustainable competitive advantage of SMEs in food and beverage sector in Kenya. The study therefore recommends that SMEs owners and managers should develop and utilize strategies to enhance their conceptual skills in order to achieve sustainable competitive advantage of the firms. Keywords: Manufacturing Enterprises, Conceptual Skills, Small and Medium Enterprises, Sustainable Competitive Advantage